Increased mtPDH Activity Through Antisense Inhibition of Mitochondrial Pyruvate Dehydrogenase Kinase Enhances Inflorescence Initiation, and Inflorescence Growth and Harvest Index at Elevated CO2 in Arabidopsis thaliana - Weraduwage, Sarathi M.; Micallef, Malgre C.; Marillia, Elizabeth-France; Taylor, David C.; Grodzinski, Bernard; Micallef, Barry J. (Frontiers in Plant Science, 2016)
Mitochondrial pyruvate dehydrogenase (mtPDH) is a key respiratory enzyme that links glycolysis and the tricarboxylic acid cycle, and it is negatively regulated by mtPDH kinase (mtPDHK). Arabidopsis lines carrying either a constitutive or seed-specific antisense construct for mtPDHK were used to test the hypothesis that alteration of mtPDH activity in a tissue- and dosage-dependent manner will enhance reproductive growth particularly at elevated CO2 (EC) through a combined enhancement of source and sink activities. Constitutive transgenic lines showed increased mtPDH activity in rosette leaves at ambient CO2 (AC) and EC, and in immature seeds at EC. Seed-specific transgenic lines showed enhanced mtPDH activity in immature seeds. A strong relationship existed between seed mtPDH activity and inflorescence initiation at AC, and at EC inflorescence stem growth, silique number and seed harvest index were strongly related to seed mtPDH activity. Leaf photosynthetic rates showed an increase in rosette leaves of transgenic lines at AC and EC that correlated with enhanced inflorescence initiation. Collectively, the data show that mtPDHK plays a key role in regulating sink and source activities in Arabidopsis particularly during the reproductive phase.